Illuminating the global maize trade network: structure, resilience and supply chain security: Illuminating the global maize trade network: structure, resilience and supply chain security - Chen, Wei; Shu, Xin; Zhao, Xiquan; Yu, Hu (Food security, 2025)
This study investigates the global maize trade network from 2000 to 2022, focusing on its structure, resilience, and supply chain dynamics to improve food security. The analysis reveals significant growth in global maize trade, with the network becoming increasingly complex and dense, leading to improved efficiency. However, overall network connectivity remains uncertain, exposing vulnerabilities within the system. The trade network has developed a hierarchical structure, with four major clusters—North America-Caribbean, South America, Europe, and East Asia—dominating global trade, signaling the emergence of a multipolar trade pattern. Over time, the network has expanded eastward, with trade flows becoming more geographically diversified. Key exporters such as the United States, Argentina, and Brazil form the network’s backbone, serving as critical hubs that facilitate the flow of maize across global markets. Additionally, gateway countries like Spain play a vital role in connecting regional clusters, enhancing the overall network’s connectivity. While the resilience of the maize trade network has improved, significant node polarization remains. Central exporters remain indispensable for the network’s stability, while peripheral regions remain more vulnerable. The study underscores the importance of strengthening connectivity between key players and regions to reduce vulnerabilities and enhance the resilience of the global maize trade network. Policy recommendations are provided to ensure the sustainability and stability of the global maize supply chain, ultimately supporting global food security in the face of growing demand and potential disruptions.